If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4(2.5x+8.7)=(1.4-9.2x)(6)
We simplify the equation to the form, which is simple to understand
-4(2.5x+8.7)=(1.4-9.2x)*(6)
Reorder the terms in parentheses
+(-10x-34.8)=(1.4-9.2x)*(6)
Remove unnecessary parentheses
-10x-34.8=+(+1.4-9.2x+)+*(+6+)
Reorder the terms in parentheses
multiplication of parentheses
-10x-34.8=(+8.4-55.2x)
Remove unnecessary parentheses
-10x-34.8=+8.4-55.2x
We move all terms containing x to the left and all other terms to the right.
-10x+55.2x=+8.4+34.8
We simplify left and right side of the equation.
+45.2x=+43.2
We divide both sides of the equation by 45.2 to get x.
x=0.955752212389
| 5x^2+9x-72= | | 9h=49 | | 7-5x-5-7x=5 | | 3-0.4k=3 | | s^3-3s^2-3=0 | | -3(x-2)=x | | 81x^2-9y^2= | | 5x^1=1 | | 15+5=-2(9x-10) | | x/4=5 | | 9x+28=7x+24 | | solve(x-1)(2x-5)=9 | | 16(3x-2)=4(12x+4) | | 15x-20+35x=180 | | 10x=-15 | | 10=-15 | | 10-(2n-5)=2-3n | | Y=X^2+7x-8 | | 6y-7=7y-6 | | 3x^2+17x+24=0 | | x+25+55=180 | | x=40y | | 10v^2-21=0 | | x=-3.5+0.5y | | -3x^2+343=0 | | 5p-4(1-3p)=4p-(p+1) | | x^2+8x+7=-8 | | 3xy^2*2x^0= | | x^3+(4*x^2)+4*x=0 | | 2x(4-7x)-x(4x+5)=4x+81 | | 6b+7=-5 | | 9x^2-28x-28=0 |